Socio-economic status and inequalities in children's IQ and economic preferences - Thomas Deckers; Armin Falk; Fabian Kosse; Pia Pinger; Hannah Schildberg-Hörisch (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
This paper explores inequalities in IQ and economic preferences between children from high and low socio-economic status (SES) families. We document that children from high SES families are more intelligent, patient and altruistic, as well as less likely to be risk-seeking. To understand the underlying causes and mechanisms, we propose a framework of how parental investments as well as maternal IQ and economic preferences influence a child's IQ and preferences. Within this framework, we allow SES to influence both the level of parental time and parenting style investments, as well as the productivity of the investment process. Our results indicate that disparities in the level of parental investments hold substantial importance for SES gaps in economic preferences and, to a lesser extent, IQ. The systematic variations in IQ and preferences by SES might offer an explanation for socio-economic disparities in economic decision-making and social immobility.
Keywords: C90; D64; D90; D81; J13; J24; J62; 330; socio-economic status; time preferences; risk preferences; altruism; experiments with children; origins of preferences; human capital